Troponin - factor for determination of myocardial ishemic damage in postoperative period of cardiac surgery in pediatric population - Hristina Mandzukovska; A. Sofijanova; K. Maneva; V. Chadikovski; Lj. Kojikj; Radica Muratovska-Delimitova; M. Kimovska Hristova; S. Naunova-Timovska; T. Voinovska; S. Neshkova; B. Gjurkova; V. Jovanovska; et al. (Macedonian Association of Anatomists and Morphologists, 2016)
Background: Troponin is an important biomarker for early evidence of ischemic damage to the heart tissue after a cardiac surgery conducted in the pediatric and adult populations. Elevated values correlate with perioperative and postoperative procedures and practices and are a significant factor for possible later complications. Methods: 30 operated children divided into two groups, the first group of operated children without a cardiopulmonary bypass CPB, and the second group of operated children with a cardiopulmonary bypass. A correlation between elevated troponin and perioperative and postoperative parameters was followed (duration of CPB and aortic cross-clamping time, stay in the intensive care and therapy during respiratory support, during inotropic support, the presence of renal or hepatic failure, postoperative complications). Results: In both groups of operated children the troponin was elevated. In the first group of children operated without cardiopulmonary bypass, the average value of troponin was 9,5ng/ml (range 6,5-16,8 ng/l). In the second group of operated children (27 children) with cardiopulmonary bypass, the mean valueof duration was 81.5 minutes (range 18 to 296 minutes), and X-cross time (aortic cross-clamping time) at the same children is with a mean value of 28,2 minutes (range of 0-86 min.). At the first group of children the troponin was with a mean value of 9,5ng/ml and in the second group with a mean value of 23,0 ng/ml. The obtained values of troponin have confirmed a highly significant correlation with perioperative and postoperative procedures. Conclusions: Troponin is a prognostic marker for early evidence of ischemic and necrotic changes of cardiac infarction in the pediatric population in cardiac surgery. Elevated values in the first 24-48 hours are significantly correlated with perioperative and postoperative procedures and are an important indicator of the extent of damage to the heart tissue. But its prognostic significance of myocardial ischemic changes is lost in a period between 2-6 months after the cardiac surgery.
Keywords: troponin; cardiac surgery; myocardial ischemic changes